2000
DOI: 10.1002/(sici)1097-0088(200001)20:1<47::aid-joc461>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

On the relationships between ENSO and autumn rainfall in Iran

Abstract: An investigation of the relationships between Iranian autumn rainfall and the El Niño–Southern Oscillation (ENSO) phenomenon was explored for the period 1951–1990. A negative correlation between the Troup Southern Oscillation Index (SOI) and rainfall data was found for almost all of Iran. The relationships were found to be stronger and more consistent over some regions comprising the southern foothills of the Alborz Mountains, northwestern districts and central areas. For the other parts of the country, correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(31 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…Several studies have indicated that the ENSO is teleconnected to the rainfall variability in different parts of the world (Parthasarathy and Pant, 1984;Janowiak, 1988;Parthasarathy et al, 1988;Allan and Pariwono, 1990;Tapley and Waylen, 1990;Lough, 1992Lough, , 1997Hastenrath et al, 1993Hastenrath et al, , 1995Allan et al, 1995;Camberlin, 1995Camberlin, , 1997Gingras and Adamowski, 1995;Seleshi and Demaree, 1995;Glantz, 1996;Piechota and Dracup, 1996;Sun and Furbish, 1997;Chiew et al, 1998;Nazemosadat andCordery, 2000, Sewell andLandman, 2001). A brief historical review about the development of the ENSO teleconnections can be found in Goddard et al (2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that the ENSO is teleconnected to the rainfall variability in different parts of the world (Parthasarathy and Pant, 1984;Janowiak, 1988;Parthasarathy et al, 1988;Allan and Pariwono, 1990;Tapley and Waylen, 1990;Lough, 1992Lough, , 1997Hastenrath et al, 1993Hastenrath et al, , 1995Allan et al, 1995;Camberlin, 1995Camberlin, , 1997Gingras and Adamowski, 1995;Seleshi and Demaree, 1995;Glantz, 1996;Piechota and Dracup, 1996;Sun and Furbish, 1997;Chiew et al, 1998;Nazemosadat andCordery, 2000, Sewell andLandman, 2001). A brief historical review about the development of the ENSO teleconnections can be found in Goddard et al (2001).…”
Section: Introductionmentioning
confidence: 99%
“…The term 'El Niño' is used to describe the quasi-cyclic heating of the Pacific Ocean, and the term 'southern oscillation' is used to describe the undulations in the atmospheric pressure at sea level across the Pacific Ocean. The warm phase of the ENSO is known as El Niño and its cold phase is known as La Niña (Nazemosadat and Cordery, 2000). The ENSO is usually described by numerical indices, which utilize the changes in the sea-level pressure or anomalies of the SST in the Pacific Ocean (Kawamura et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…However, other parts of the globe, such as the Middle East, are not as strongly associated with the ENSO phenomenon (Ropelewski and Halpert, 1987;Ropelewski and Halpert, 1989). Notwithstanding, Nazemosadat and Coredy (2000) have documented an ENSO signal in Iran during the OND season, and Barlow et al (2002) reported that severe droughts that occurred in central south Asia from 1998 to 2001 are related to a combination of the La Niña and the unusually warm SSTs in the west Pacific, which may have enhanced the regional dynamics of the warm pool. Nazemosadat and Ghasemi (2004) reported that warm ENSO phases reduce the intensity and probability of drought while the cold ENSO phases increase the intensity and probability of severe drought during OND, particularly over the southern parts of Iran.…”
mentioning
confidence: 99%
“…A central source of inter-annual climate variability over much of the globe is the ENSO events [e.g., 47,48,50]. In recent decades [50,[59][60][61][62][63] it has been indicated that the teleconnection of ENSO has indeed extended its reach into the Middle East region. They noted an increase in the impact of El Niño on rainfall patterns in the middleeast.…”
Section: Influence Of the Enso On The Climate Of Saudi Arabiamentioning
confidence: 99%